2018
DOI: 10.7717/peerj.5053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extended spectrum beta lactamase and plasmid mediated quinolone resistant genes in strains of Klebsiella pneumonia, Morganella morganii, Leclercia adecarboxylata and Citrobacter freundii isolated from poultry in South Western Nigeria

Abstract: A serious concern is arising on the coexistence of extended-spectrum beta-lactamase (ESBL) and plasmid mediated quinolone resistance (PMQR) producing bacteria in animal husbandry, which could be transferred to humans, especially in strains that may not be routinely screened for resistance. This study therefore tested the prevalence of ESBL and PMQR genes in selected bacteria isolated from poultry faeces. Faecal droppings of birds were collected from 11 farms in five states in South Western Nigeria. Bacteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
9
17
1
Order By: Relevance
“…Beta-lactamase genes were detected among the isolates. These genes have previously been detected in poultry [3436]. The TEM gene predominated followed by CTX-M; this was similar to previous study in Nigeria that reported prevalence of 63% and 35% of TEM and CTX-M respectively in isolates from chicken droppings [34].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Beta-lactamase genes were detected among the isolates. These genes have previously been detected in poultry [3436]. The TEM gene predominated followed by CTX-M; this was similar to previous study in Nigeria that reported prevalence of 63% and 35% of TEM and CTX-M respectively in isolates from chicken droppings [34].…”
Section: Discussionsupporting
confidence: 84%
“…These genes have previously been detected in poultry [3436]. The TEM gene predominated followed by CTX-M; this was similar to previous study in Nigeria that reported prevalence of 63% and 35% of TEM and CTX-M respectively in isolates from chicken droppings [34]. In contrast, high prevalence of OXA has been reported in Algeria while in Germany the predominant beta-lactamase gene was CMY-2 and SHV [37, 38].…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of extended-spectrum-beta-lactamaseproducing (ESBL) and quinolone resistance Enterobacteriaceae is increasing all over the world and infection with these bacteria strains were associated with an increase of morbidity, mortality, and health care costs [14,15]. In the USA, the Centers for Disease Control and Prevention demonstrated in 2013 an increase in drug-resistant microorganisms and approximately 26,000 ESBL-producing Enterobacteriaceae infections and 1700 death s [16].…”
Section: Introductionmentioning
confidence: 99%
“…The excreta samples were thawed at room temperature and each 1 g sample was diluted in 4.5 mL Buffered Peptone Water (BPW, Carl Roth GmbH + Co. KG, Germany) as described previously [28]. The dilutions were plated on multiple MacConkey agar plates containing 2 µg CTX/mL agar as described previously [29][30][31] and incubated aerobically at 37 • C for 48 h.…”
Section: Prevalence Of Esbl-producing Enterobacteriaceaementioning
confidence: 99%